Carpal tunnel syndrome during the third trimester of pregnancy: prevalence and risk factors - Oliveira, Gladys Alexandra Dias de [UNESP]; Bernardes, João Marcos [UNESP]; Santos, Elisiane de Souza [UNESP]; Dias, Adriano [UNESP] (Springer Nature, 2019)
Purpose: To estimate the prevalence of indicative signs and symptoms of carpal tunnel syndrome (CTS) during the third trimester of pregnancy; assess the severity of symptoms and functional impairment; evaluate associated factors; and to evaluate the complaint of CTS in pregnant women through ultrasonography (USG). Methods: A cross-sectional study, in which participants were classified into two groups: presence and absence of indicative signs and symptoms of CTS. Severity of symptoms and functional status was assessed by the Boston Carpal Tunnel Questionnaire. USG was performed by multiplanar technique of static and dynamic evaluation. Association between USG and indicative signs and symptoms of CTS was estimated using Fischer's exact test and Poisson regression models were used to estimate the association of exploratory variables and indicative signs and symptoms of CTS. Results: Altogether, 482 women were recruited and 111 presented indicative signs and symptoms of CTS, resulting in a prevalence of 23.03%. USG was not able to distinguish indicative signs and symptoms of CTS groups. Both the severity of the symptoms and the impairment of the manual function were mild. Being left-handed, gestational diabetes mellitus and maternal age were associated with indicative signs and symptoms of CTS. Conclusions: The high prevalence of indicative signs and symptoms of CTS and the difficulties that they can cause reinforce the importance of adequate diagnosis and treatment. Further studies are needed to assess the value of USG as a diagnostic method for CTS during pregnancy.
Keywords: Carpal tunnel syndrome; Functional laterality; Gestational diabetes; Maternal age; Pregnancy; Prevalence